A Critical Analysis of Gods Righteousness in Romans 1: 16-17 - Halim Wiryadinata (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2014)
This article brings the new approach for the book of Romans especially the word of Gods righteousness is the central pint point for the theology of the Apostle Paul. Gods righteousness is another attempt for solving the arguments of interpreting the book of Romans.